Analytical and numerical investigation of a low-damage uplift friction damper for self-centering cross-laminated timber rocking walls. (1st March 2022) - Tatar, Arman; Dowden, Daniel M.
Highlights: Uplift friction damper for seismically resilient cross-laminated timber rocking walls. Preliminary parametric study highlights friction damper tunability. Friction damper provides stable energy dissipation and self-centering capability. Abstract: Cross-Laminated Timber (CLT) rocking wall systems have gained considerable attention in recent years as a potential Seismic-Force Resisting System for mass timber construction in regions of moderate to high seismic risk. It is well understood that CLT rocking walls do not provide any measurable amount of ductile energy dissipation on their own but instead rely on energy dissipation through their connections. A common approach has been to provide replaceable metallic yielding elements or structural fuses located at the base of the wall or the vertical interface between coupled walls. However, hysteretic yielding dampers are susceptible to both strength and stiffness degradation. To overcome these limitations, this paper presents a newly proposed Uplift Friction Damper (UFD) as an alternative to hysteretic dampers installed at the base of CLT rocking walls. The proposed UFDs provide stable energy dissipation and enhanced self-centering capability. This paper presents details of the UFD device along with analytical and continuum finite element numerical models that inform the kinematic response of the UFD. Furthermore, the tunability of the UFD device is investigated by changing select governing parameters of the UFD in a limited parametric study. First, the fundamental response of a single UFD device is presented to inform the basic local response. Next, the system response of the UFD installed on a SC-CLT wall is investigated through cyclic pushover analyses using continuum finite element models. Results show that the amount of energy dissipation depends primarily on the inclination angle of the friction interface, stiffness of the bolt-disc springs providing the normal clamping force, and coefficient of friction between the sliding interfaces.